Comparison of bacterial vaginosis symptoms reported in social media vs. those reported by patients - Velmahos, Andriana H.; Cooley Demidkina, Briah; Mitchell, Caroline M. (Frontiers in Reproductive Health, 2025)
IntroductionThere is an increasing tendency to seek health information online rather than through medical professionals. However, the easy accessibility of information online allows for an increased risk of encountering medical misinformation.MethodsWe compared descriptions of symptomatology of bacterial vaginosis (BV) on four social media platforms: Instagram, Facebook, YouTube and X (Twitter). We then compared the frequency of discussion of symptoms with patients' report of symptoms in clinically diagnosed BV, vulvovaginal candidiasis and vulvodynia.ResultsSocial media was more likely to report burning (45% of posts), itching (45%) or pain (23%) as symptoms of BV than patients (moderate-severe itching 30%, burning 21% or pain 21%). Although pain was reported more often by people with vulvodynia, other symptoms were not different across diagnoses.DiscussionSocial media overemphasizes the ability of symptoms to allow self-diagnosis of vaginitis, which can lead to delayed treatment, highlighting the need to promote accurate health information online.